The Influence of Ad Creativity, Message Quality, and Viewing Frequency on Consumer Purchase Intention: Case Study on Students of Universitas Perjuangan Tasikmalaya: The Influence of Ad Creativity, Message Quality, and Viewing Frequency on Consumer Purchase Intention: Case Study on Students of Universitas Perjuangan Tasikmalaya - Saputra, Jumadil; Sidiq, Fahmi (Communication In Research And Publications, 2023)
This research focuses on advertising effectiveness by considering three key variables, namely advertising creativity, message quality, and viewing frequency. The main objective of the study is to assess the influence of these advertising effectiveness variables, which include Advertising Creativity, Message Quality, and frequency views, on consumer purchase intention. In addition, this study also aims to identify which variables are dominant in influencing consumer purchase intentions. This study uses the Multiple Linear Regression analysis method with the help of SPSS software version 22.0. The research population consists of students of Universitas Perjuangan who have watched Mi Indomie television advertisements at least 3 times. The research sample consisted of 170 respondents selected using non-probability sampling technique with accidental sampling method, namely by distributing questionnaires as a data collection tool. The results showed that the variables of advertising creativity, message quality, and frequency of ad viewing have a positive and significant influence on consumer buying interest. The results of the analysis also indicate that the advertising creativity variable is the most dominant variable in influencing consumer buying interest. Thus, this study provides further understanding of how advertising effectiveness, especially through improving advertising creativity, message quality, and frequency of ad serving, can increase consumer purchase intention. These findings can be a valuable guide for advertising and marketing practitioners in designing more effective advertising campaigns.